MORPHOLOGICAL RESPONSES OF LETTUCE CULTIVARS UNDER WATER DEFICIENCY - Urbano Júnior, Sidnei Antônio; Soares de Oliveira Neto, Sebastião (Revista Brasileira de Engenharia de Biossistemas, 2021)
Lettuce is the main hardwood consumed in Brazil. Water deficit is one of the main crop productivity reducers, affecting several areas of the planet. Although the cultivation of lettuce is almost entirely carried out in irrigated areas, if for some reason there is a lack of water for the plants, several damages can be observed in the crop. The objective of this work was to evaluate lettuce cultivars and verify the agronomic performance and the effects of moderate water deficit on the morphological traits of the crop. The experiment was carried out in randomized blocks in a factorial scheme, being tested four cultivars (Jade, Vanda, Loreane, and Valentina) and the conditions with and without water deficit. Cultivars Loreane and Valentina showed superior results for shoot length and shoot dry mass, while cultivar Jade showed higher number of leaves and therefore can tolerate moderate water deficit in the early stages of the crop.